PENINGKATAN PENGETAHUAN MASYARAKAT MENGENAI HIPERTENSI DI PUSKESMAS OLAK KEMANG, DANAU TELUK KOTA JAMBI - Lipinwati; Hasna Dewi; Samsirun Halim; Hafizah; Denok Tri Hardiningsih; Attiya Istarini; Wulandari, Putri Sari; Amatullah, Afifah (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2024)
Hypertension significantly increases the risk of heart, brain and kidney diseases, and is one of the top causes of death and disease throughout the world. One of the global targets for noncommunicable diseases is to reduce the prevalence of hypertension by 33% between 2010 and 2030. This Community Service Activity (CSA) was conducted at the Olak Kemang Health Center. The purpose of this Community Service is the prevention and control of Hypertension by increasing the participation and level of knowledge of the community in Danau Teluk Village through health education and blood pressure checks. The activity was attended by 66 participants, participants were given pretest and posttest questions to measure knowledge about hypertension. The results showed an increase in the knowledge of community service participants after being given counseling about hypertension (p-value 0.000).